The Escalation of Organizational Moral Failure in Public Discourse: A Semiotic Analysis of Nokia's Bochum Plant Closure - Lauri Wessel; Riku Ruotsalainen; Henri A. Schildt; Christopher Wickert (Journal of Business Ethics, 2022)
We examine the processes involved in the escalation of a plant closure from a local concern to a perceived organizational moral failure that commands national attention. Our empirical case covers the controversy over the decision of telecommunications giant Nokia to close a plant in Germany, despite having received significant state subsidies, and the relocation of production to Hungary and Romania. We conducted an inductive study that utilizes a semiotic analysis to identify how various actors framed the controversial plant closure and sought to cast it as moral failure. Our analysis uncovered two distinctive moral framings of the plant closure and revealed how key actors used evocative labels to frame these events in moral terms. These moral framings drew in additional stakeholders, generated more widespread media coverage, and turned the case into an organizational moral failure in the eyes of the national public. We contribute to the literature on organizational moral failure by theorizing its escalating process and elaborating why and how local events may become moral issues of interest to broader stakeholder groups.
Keywords: 300; Process study; Media; Nokia; Organizational moral failure; Plant closure